Novel magnetodielectric cobalt ferrite–titania–silica ceramic composites with tunable dielectric properties. Issue 15 (15th November 2016) - Galizia, Pietro; Gardini, Davide; Ortelli, Simona; Capiani, Claudio; Anbinderis, Maksimas; Grigalaitis, Robertas; Maizza, Giovanni; Galassi, Carmen
Abstract: The cobalt ferrite (CF)–titania (TiO2 )–silica (SiO2 ) system has been studied to produce new ceramic composites by conventional solid state reaction. The microstructure of the sintered CF–TiO2 –SiO2 mixture has been related to compositional modifications in terms of SiO2 /TiO2 weight ratio keeping constant the CF weight percentage. Microstructural characterization of the sintered bodies was performed in order to understand microstructure evolution, and to quantify the phases volume fraction. The final compositions after sintering differ significantly from the starting ones as a consequence of the reaction of titania with the ferrite, and the formation of the ilmenite-type CoTiO3 . Four different distributed phases are present, depending on the starting SiO2 /TiO2 weight ratio. The complex permittivity dispersion of ceramic composites was investigated and correlated to their microstructure. Lastly, CF-SiO2 magneto-dielectric composites are suggested as possible candidates for high frequency applications as miniaturized antennas.